ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN CINCIN RIBEKA TERHADAP PEMAHAMAN NUMERASI DAN KESADARAN LINGKUNGAN SISWA KELAS V SEKOLAH DASAR - Hartik, Hartik; Wiryanto, Wiryanto; Mariana, Meni; Hendratno, Hendratno; Istiq’faroh, Nurul (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
The aim of this research was to analyze initial needs in developing concrete learning media in the form of Ribeka Rings to improve numeracy understanding and environmental awareness for fifth grade of elementary school students. The condition of the school environment was not kept clean and the students' low awareness of waste management can be overcome through the integration of numeracy learning with the use of recycled waste as a concrete medium. Environmental awareness that is formed through the use of recycled waste as a learning medium can be strengthened with a collaborative approach, where teachers, students and the community jointly design and create ribeka ring media in order to increase students' understanding of numeracy and environmental awareness in the school. The method used in this research is a descriptive approach with data collection techniques through observation, interviews and questionnaires for teachers and students. The research results show that students need learning media that can visualize mathematical concepts in a concrete and fun way. These findings supported the development of Ribeka Ring media as an effective means of increasing understanding of numeracy while instilling environmental awareness in elementary school students. Learning media that combines mathematical concepts with environmental awareness, such as the Ribeka Ring, can be an effective solution for improving students' understanding of numeracy and environmental awareness simultaneously. It is hoped that this media can make learning more fun and relevant to real life.